Evaluation of effectiveness of training and development: The Kirkpatrick model - Mohammed Saad, AlYahya; Mat, Norsiah (Society for Business Research Promotion, 2013)
Evaluation of training effectiveness is the measurement of improvement in the employee’s knowledge, skill and behavioral pattern within the organization as a result of training program. This measurement help to match the cost incurred in the design and implementation of training with the associated benefits.Thus, it indicates whether the program has been able to deliver its intended goals and objectives. The purpose of this paper is to review the model of training effectiveness for the adoption by the human resources development executives in their planning, designing and implementation training program.